2016
DOI: 10.1126/scitranslmed.aaf3006
|View full text |Cite
|
Sign up to set email alerts
|

Delayed globin synthesis leads to excess heme and the macrocytic anemia of Diamond Blackfan anemia and del(5q) myelodysplastic syndrome

Abstract: Diamond Blackfan anemia (DBA) and myelodysplastic syndrome (MDS) with isolated del(5q) are severe macrocytic anemias; although both are associated with impaired ribosome assembly, why the anemia occurs is not known. We cultured marrow cells from DBA (n = 3) and del(5q) MDS (n = 6) patients and determined how heme (a toxic chemical) and globin (a protein) are coordinated. We show that globin translation initiates slowly, whereas heme synthesis proceeds normally. This results in insufficient globin protein, exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
87
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(110 citation statements)
references
References 51 publications
19
87
1
Order By: Relevance
“…In order to demonstrate that increased apoptosis in patient cells treated with ALA was due to heme overload, we performed rescue experiments by reducing intracellular heme loading. It has been previously reported that Hemopexin (HX) facilitates heme export through FLVCR1[31, 32]. Thus, we added HX to the medium.…”
Section: Resultsmentioning
confidence: 99%
“…In order to demonstrate that increased apoptosis in patient cells treated with ALA was due to heme overload, we performed rescue experiments by reducing intracellular heme loading. It has been previously reported that Hemopexin (HX) facilitates heme export through FLVCR1[31, 32]. Thus, we added HX to the medium.…”
Section: Resultsmentioning
confidence: 99%
“…Delayed expression of globin genes in primary DBA cells has been reported to lead to accumulation of free heme and heme toxicity, which perturbs erythroid differentiation (26). We show that knockdown of RPS19 in CD34 + progenitors rapidly inhibited expression of globin transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al in an elegant study showed that disruption of ribosomal assembly as a result of RPS14 haploinsufficiency slows protein synthesis and impairs globin production relative to heme production. This discordant production rate results in excess heme in erythroid colony‐forming units (CFU‐E)/proerythroblasts with consequent excessive generation of reactive oxygen species (ROS), leading to cell death as well as early termination of erythropoiesis by decreasing GATA1 and impeding mitosis . In further support of this mechanism, these investigators showed that once heme synthesis was impaired by restricting iron availability or by facilitating excess heme export through feline leukemia virus subgroup C receptor (FLVCR), erythropoiesis was improved .…”
Section: Rps14 Haploinsufficiency Results In Anemiamentioning
confidence: 99%
“…This discordant production rate results in excess heme in erythroid colony‐forming units (CFU‐E)/proerythroblasts with consequent excessive generation of reactive oxygen species (ROS), leading to cell death as well as early termination of erythropoiesis by decreasing GATA1 and impeding mitosis . In further support of this mechanism, these investigators showed that once heme synthesis was impaired by restricting iron availability or by facilitating excess heme export through feline leukemia virus subgroup C receptor (FLVCR), erythropoiesis was improved . Transfusion‐dependent anemia is a significant aspect of del(5q) MDS morbidity that impacts quality of life, and these breakthroughs elucidating the molecular pathogenesis have ushered in investigational therapies that may restore effective erythropoiesis and improve the patient's quality of life.…”
Section: Rps14 Haploinsufficiency Results In Anemiamentioning
confidence: 99%